A dependency annotation scheme for Bangla treebank. - Chatterji, Sanjay; Sarkar, Tanaya; Dhang, Pragati; Deb, Samhita; Sarkar, Sudeshna; Chakraborty, Jayshree; Basu, Anupam (Language Resources & Evaluation, 2014)
Dependency grammar is considered appropriate for many Indian languages. In this paper, we present a study of the dependency relations in Bangla language. We have categorized these relations in three different levels, namely intrachunk relations, interchunk relations and interclause relations. Each of these levels is further categorized and an annotation scheme has been developed. Both syntactic and semantic features have been taken into consideration for describing the relations. In our scheme, there are 63 such syntactico-semantic relations. We have verified the scheme by tagging a corpus of 4167 Bangla sentences to create a treebank (KGPBenTreebank).